DEVELOPING ESP TEXTBOOK FOR CULINARY SKILLS PROGRAM OF VOCATIONAL HIGH SCHOOL USING TASK-BASED LANGUAGE TEACHING - Novitasari Novitasari; Joko Nurkamto; Diah Kristiana (Sekolah Tinggi Teknik Malang, 2017)
This research aims at developing English for Specific Purposes (ESP) textbook to fulfil the students’ need toward the material at vocational high school using Task-based Language Teaching (TBLT). It was conducted to investigate (1) the quality of the existing course book used in vocational high school, (2) the development of the ESP textbook using TBLT in vocational high school in Pacitan, East Java. The research design used in this research is Research and Development (R&D) proposed by Borg and Gall. This study was oriented to the product development in the form of procedural model and was conducted in two main phases namely (1) exploration phase and (2) product development phase. The exploration phase revealed: (1) the description of the existing course book used in vocational high school and (2) the need analysis of the ESP learning material. While the product development phase explained; (1) the description of the draft of ESP textbook, (2) the result of the trial of the draft, and (3) the final draft of ESP textbook. The data in the exploration stage were collected through conducting document analysis, and having interview. It was carried out to reveal the quality of existing course book used at vocational high school and the learner’s need toward material. The findings show that the course book used at the vocational high school students contains general English material and it is less specific to be used for the students of culinary skill program. Hence, the findings imply the ESP textbook was needed to be developed by considering the need of the teacher and the students. The ESP textbook was developed by considering some aspects. It contains theoretical theories of ESP and TBLT. Then, it was validated and reviewed by some experts on English language teaching and implemented in class. Through conducting observation, distributing questionnaire, and having focus group discussion that involved the researcher, the teacher, the expert and the students, the draft was revised to be the final draft of ESP textbook. Therefore, after going through the stages, it could be said that the draft is feasible to be applied as supplementary material to teach students of culinary skills program in vocational high school.